Analisis Komitmen Dan Kemampuan Pelaku Usaha Marketplace Terhadap Peraturan Pemerintah Nomor 80 Tahun 2019 - Wicaksena, Bagus (Cendekia Niaga, 2022)
The potential of Indonesia's e-commerce sector is estimated to reach US$ 137.5 billion by 2025 and become the largest in the Asia Pacific region. Currently, the development of the e-commerce sector is regulated in Government Regulation Number 80 of 2019 concerning Trade through Electronic Systems (PP PMSE). This analysis aims to see the level of commitment and ability of marketplace actors in complying with the provisions in PP PMSE, considering their dominant role in Indonesia’s e-commerce. By using the Rule, Opportunity, Capacity, Communication, Interest, Process, Ideology (ROCCIPI) approach, respondents perceive that licensing, personal data protection, and consumer protection are clear and in accordance with the commitment and ability of the respondent. However, respondents' perceptions regarding the sale of domestic products and the practice of fair business competition need to be addressed so as to provide a clear reference. Regulations will be effective if they can foster the commitment and capability of business actors. Therefore, the essence of the policy recommendations is to focus on efforts to increase sales of domestic products as well as supervision that supports fair and sound competition. Since the commitment and capability of business actors to comply will determine effective regulations, the Co-Regulation approach needs to be used in the policy-making process by prioritizing Public Private Dialogue (PPD) that optimizes existing regulations, and harmonizes with the direction of global cooperation in e-commerce development.